MgH lines in the spectrum of Arcturus - Kushniruk, I.O.; Pavlenko, Ya.V.; Kaminskiy, B.M. (Advances in Astronomy and Space Physics, 2013)
The synthetic spectra of MgH lines were computed for the grid of the model atmospheres and compared with the observed spectrum of Arcturus. The parameters of the atmosphere of Arcturus for log g = 1.5 and Tₑff = 4300K were via minimization of deviation between observed and computed spectra and compared with the results of other studies.